The policy education and training of quality as dampening economic crises. (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Today, few doubt the social character who has the right to education and the need that this fundamental right is met at the global level in the best possible way; moreover, from the economic point of view, does not create any controversy regarding the role that the education and training on growth and economic development of countries. Despite this, when moments of economic crisis, there is a tendency to neglect education policy and training without realizing is that this is an automatic damper to prevent the negative effects that are generated with these crises. This article will discuss how evolved the policy of education and training a Social policy, with a view to the fulfilment of a fundamental right, to an economic vision that education and training, along with the possible research, development and innovation, they are fundamental instruments for growth and economic development. In addition, education will be exposed to what extent and training have been gaining importance within the economic sphere. To analyze this issue will prove the evolution that has taken in the European Union policy of education and training, as it is one of the environments in which more clearly shows how this policy has gone from being a complementary tool to make some economic objectives, considered to be one of the fundamental pillars in the new European strategy. Finally, to reinforce the importance that has this policy stands an aspect little considered in relation to education and training: dampens economics crises. This function is not usually take into account when he speaks of policies anti-crisis short-term. However, it is essential to consider it since you can avoid many of the negative socio-economic effects that occur in these crisis situations. This cushion character gives to education policy and training, especially for quality, a new role within the socio-economic policies that apply traditionally countries and requires a reconsideration of the place the same within these.
Keywords: education policy and training; research; development and innovation policy; social capital; human capital; technological capital; economic growth and development; economic crises.